PENDIDIKAN KEWARGANEGARAAN DAN LITERASI MEDIA DALAM MENCERDASKAN NETIZEN DI MEDIA SOSIAL - Luh Suryatni (JURNAL MITRA MANAJEMEN, 2019)
Netizens and social media are very important factors in the development of technology and information through information systems as the information conveyed in cyberspace does not only affect the life of a country, it can even affect the world. In anticipating negative factors where netizens are also human beings who have emotions and selfish qualities, it is necessary to process civic education and media literacy to provide knowledge and skills in character building, so that they have ethics in surfing. The purpose of this paper is to discuss how civic education and media literacy can educate netizens by thinking creatively and wisely in conveying information on social media. The data collection method used is a literature review with descriptive analysis techniques. The results of the study showed that civic education and media literacy can influence netizens’ way of thinking to be wiser and more ethical before posting or sharing information on social media.Keyword: Civic Education, media literacy, netizen, social media.